Good judgment in public accounting: Quality and justification* - EMBY, CRAIG; GIBBINS, MICHAEL (Contemporary Accounting Research, 1987)
Abstract. A description of factors contributing to good judgment is developed by considering both the process of exercising judgment and the results of having exercised it. Factors are developed from public accountants' perceptions of important components in characterizing good professional judgment in public accounting. Descriptive data about important judgment quality factors are presented and hypotheses concerning justification are tested using responses to a process‐oriented questionnaire. The emphasis is on the natural environment of the professional accountant and the types of judgment situations which occur in the field, with reliance on respondents to interpret their own comments. The questionnaire results provide a description of judgment factors which professional accountants see as important. Factor categories related to expectation, outcome, and justification perspectives on judgment quality are shown to play a role in defining good judgment, with variations related to position (level of responsibility) in the accounting firm. The results also indicate that justification is perceived differently by people in different positions. Résumé. Les auteurs décrivent les facteurs contribuant à la qualité du jugement en prenant en considération à la fois le processus d'exercice du jugement et les résultats de ce processus. Ces facteurs ont été déterminés à partir des éléments perçus par les experts‐comptables comme étant importants dans la définition de ce qu'est un bon jugement professionnel, en expertise comptable. Les auteurs présentent des données descriptives au sujet des principaux indices de qualité du jugement et testent certaines hypothèses relatives à la justification, à partir de réponses à un questionnaire axé sur le processus. Ils s'intéressent à l'environnement naturel du comptable professionnel et aux cas de jugement qu'on retrouve dans la pratique, en confiant aux répondants le soin d'interpréter leurs propres observations. Les résultats du questionnaire offrent une description des facteurs que les comptables professionnels jugent importants dans l'évaluation de la qualité d'un jugement. Il semble que les catégories de facteurs reliées à une évaluation en termes d'attentes, de résultats et de justification jouent un certain rôle dans la définition de ce qu'est un bon jugement, qui varie selon le poste occupé (niveau de responsabilité) à l'intérieur du cabinet comptable. Les résultats indiquent également que l'on perçoit la justification différemment selon le poste.